Utilization of indigenous gurgure (Monotheca Buxifolia) waste seeds as a potential feedstock for biodiesel production using environmentally benign bismuth modified CaO catalyst - Farooq, M. (Institution of Chemical Engineers, 2022)
Herein, we report the synthesis of Bi2O3 modified CaO heterogeneous catalyst for biodiesel production from low valued gurgure (Monotheca Buxifolia) seed oil to develop profitable and sustainable approach. The catalysts were analyzed by X-ray diffractometer (XRD), Brunauer-Emmett-Teller (BET), Temperature programming desorption of CO2 (TPD-CO2), Field emission scanning electron microscopy (FESEM), Energy dispersive X-ray (EDX). The activity evaluation results indicated that the CaO-Bi2O3 catalyst enriched with 20 wt Bi2O3 loading displayed an excellent catalytic performance providing biodiesel yield of 98.7 under optimum reaction parameters of oil to methanol molar ratio 1:12, 65 Â°C reaction temperature in 2 hr of reaction time and catalyst loading of 6 wt. The catalyst depicted better reusability upto six reaction cycles and hence the cost of the biodiesel could be reduced effectively. Response surface methodology (RSM) based on central composite design (CCD) was also applied to investigate the influence of reaction parameters. The statistical deign results showed good consistent with the experimental data, providing p-vale of 0.000 i.e. high level of significance of the model. Finally, it could be summarized that the synthesized catalyst demonstrated remarkable activity and durability in term of biodiesel yield using gurguray oil as a cheap and non-edible feedstock. Â© 2022 Institution of Chemical Engineers